Durability Properties of Concrete Produced by Marble Waste as Aggregate or Mineral Additives - ARTIR, RECEP (ELSEVIER SCIENCE BV, 2016)
In recent years, the growth in the industrial production and the consequent increase in the corresponding consumption have led to a fast decline in available natural resources. However, a high volume of the industrial production has generated a considerable amount of waste materials which have a number of adverse impacts on the environment. In this regard, the marble industry produces a huge amount of waste in the last decades and grows significantly in time. The marble waste is generally a highly polluting type of industrial wastes due to its highly alkaline nature and its manufacturing and processing techniques, all of which impose serious health threats to the surroundings. In this study, effects of waste marble on some durability properties such as water absorption and permeability, chloride penetration and carbonation, sulphate attack and abrasion resistance, and lastly performance at high temperature and freezing and thawing cycles of conventional or self-compacting concrete were investigated. As a result, it was found out that the use of waste marble in the conventional or self-compacting concrete mix as an admixture material or aggregate is suitable as it can improve durability properties of the concrete. Especially, properties of water absorption & permeability and resistance of chloride penetration & sulphate attack were improved by incorporation of waste marble in concrete. (C) 2016 The Authors. Published by Elsevier Ltd.
Keywords: Concrete; marble waste; durability; admixture; aggregate; recycling; SELF-COMPACTING CONCRETE; PERFORMANCE; GRANITE